Tourism and generation Y - Benckendorff, Pierre, ....-; Moscardo, Gianna, ....- (Wallingford, Oxfordshire : Cabi, 2010)
Generation Y is a phenomenon identified by social scientists and social commentators, and is frequently discussed in the media. Referring to the current generation of young people, the label attributes to this generation modes of behaviour, values and attitudes distinct from previous generations. This book looks at Generation Y in a tourism context; in broad conceptual terms such as trends and behaviour, and in applied terms, for example looking at particular types of travel that Generation Y takes part in, and tourism marketing aimed specifically at them. This volume aims to define and examine the current and future generation of tourism workers and consumers, and will be an essential read for researchers and students in tourism studies and related industries.
Keywords: Toerisme -- Jeugd